Association between Helicobacter Pylori (H. Pylori) Infection and Esophageal Squamus Cell Carcinoma (ESCC) - J Shokry-Shirvany (Babol University of Medical Sciences, 2012)
BACKGROUND AND OBJECTIVE: Recent studies were reported that H. Pylori infection and gastric atrophy were associated with an increased risk for esophageal squamous cell carcinoma (ESCC). However this finding needs to be confirmed in other ethnic group due to the wide geographic variation of this cancer. This case-control study was designed to evaluate the association between H. Pylori infection and gastric atrophy and ESCC.METHODS: In this case-control study, 33 patients suspected with ESCC who underwent upper gastrointestinal endoscopy and confirmed by histology, and 33 sex-and age-matched controls were enrolled. Gastric atrophy and H. Pylori infection were evaluated by histology of biopsy specimens. The association between two groups was compared.FINDINGS: Twenty (60.6%) patients in case group and 8 (24.2%) in control group were infected with H. Pylori. Severe H. Pylori infection defined histologically was associated with an increased risk of ESCC (p=0.035). There was no association between gastric atrophy and ESCC in our study.CONCLUSION: Our study showed a significant relationship between H. Pylori infections and ESCC. Further studies are warranted to explore the causal relationship.